2020
DOI: 10.1002/ana.25688
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Socioeconomic Associations with Multiple Sclerosis Risk

Abstract: Objective Epidemiological research in multiple sclerosis (MS) has mainly been performed in socioeconomically and ethnically limited populations; influences on MS risk have not been studied in prospectively collected non‐White populations. We set out to study the influence of previously described MS risk factors in an ethnically diverse population. Methods A nested case–control study was created using primary care records of >1 million individuals, >50% of whom identify as Black, Asian, and Minority Ethnic (BAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
1
26
1
1
Order By: Relevance
“…Demographic details for all participants within the database were extracted, including self-declared ethnicity according to ONS codes at GP registration. Demographic details were defined as previously described [16]. Age was defined at age data extraction (1st February 2018), and deprivation according to IMD raw scores for each lower layer super output area (LSOA).…”
Section: Primary Care Data Analysismentioning
confidence: 99%
“…Demographic details for all participants within the database were extracted, including self-declared ethnicity according to ONS codes at GP registration. Demographic details were defined as previously described [16]. Age was defined at age data extraction (1st February 2018), and deprivation according to IMD raw scores for each lower layer super output area (LSOA).…”
Section: Primary Care Data Analysismentioning
confidence: 99%
“…Genome-wide association studies have found that loci in the human leukocyte antigen (HLA) region, such as HLA-DRB1 and HLA-DQA1 genes, are associated with both MS risk and elevated anti-EBNA IgG levels. [4][5][6] The possibility of confounding is suggested by studies showing that the increased MS risk associated with IM decreased in magnitude 7 or became statistically nonsignificant 8 after controlling for potential confounders, including genetic ancestry and HLA-DRB1*1501 carrier status. However, few studies have extensively addressed measured and unmeasured shared familial genetic and environmental factors as potential confounders that may be associated with both IM and MS.…”
Section: Infectious Mononucleosis (Im) Is a Clinical Manifestation Of Viral Infection Predominantly Caused Bymentioning
confidence: 99%
“…4 Multiple observational studies suggest that Hispanics with MS present at a younger age and demonstrate faster disability accumulation compared to their Caucasian counterparts of European ancestry. 5,6 However, in contrast to a burgeoning literature on racial disparities between African Americans and Caucasians with MS, there is a paucity of data on racial and ethnic variability in Hispanic populations.…”
Section: Introductionmentioning
confidence: 99%